Development of Android-Based Learning Media Using iSpring Suite to Improve Arabic Vocabulary Mastery Among Students: Pengembangan Media Pembelajaran Berbasis Android Menggunakan iSpring Suite untuk Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa - Ibnu Rawandhy N. Hula; Loni, Jabbar; Suharia Sarif (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
Purpose – This research aims to develop an Android-based Arabic learning media using iSpring Suite to enhance the Arabic vocabulary mastery of 5th-grade students at MI Terpadu Al Ishlah, Gorontalo. Design/methods/approach – The research applied the 4D Thiagarajan model for Research and Development, involving stages of definition, design, development, and dissemination. Data were collected using expert validation, questionnaires and pre-test-post-test results. Findings – The expert validation scores from language, material, and media experts were 84%, 96%, and 82% respectively, indicating the